A novel frameshift mutation in DNAH6 associated with male infertility and asthenoteratozoospermia - Huang, Fei; Zeng, Jun; Liu, Dan; Zhang, Jing; Liang, Boluo; Gao, Jingping; Yan, Rong; Shi, Xiaobo; Chen, Jianlin; Song, Wanjuan; Huang, Hua-Lin (Frontiers in Endocrinology, 2023)
Asthenoteratozoospermia is one of the most common causes of male infertility. Several genes have been identified as genetic causative factors, but there is considerable genetic heterogeneity underlying asthenoteratozoospermia. In this study, we performed genetic analysis of two brothers from a consanguineous Uighur family in China to identify gene mutations causative for asthenoteratozoospermia-related male infertility. Two related patients with asthenoteratozoospermia from a large consanguineous family were sequenced by whole-exome sequencing and Sanger sequencing to identify disease-causing genes. Scanning and transmission electron microscopy analysis revealed ultrastructural abnormalities of spermatozoa. Quantitative real-time PCR (qRT-PCR) analysis and Immunofluorescence (IF) analysis were used to assess the expression of the mutant messenger RNA (mRNA) and protein. A novel homozygous frameshift mutation (c.2823dupT, p.Val942Cysfs*21) in DNAH6 was identified in both affected individuals and was predicted to be pathogenic. Papanicolaou staining and electron microscopy revealed multiple morphological and ultrastructural abnormalities of affected spermatozoa. qRT-PCR and IF analysis showed abnormal expression of DNAH6 in affected sperm, probably due to premature termination code and decay of abnormal 3’ UTR region of mRNA. Furthermore, ICSI could achieve successful fertilization in infertile men with DNAH6 mutations. The novel frameshift mutation identified in DNAH6 may contribute to asthenoteratozoospermia. These findings expand the spectrum of genetic mutations and phenotypes associated with asthenoteratozoospermia, and may be useful for genetic and reproductive counseling in male infertility.